Geohazard-Informed Rapid Planning for Disaster Relief Operations: Lessons from Flood Response in Sumatra - Maulana, Hamzah (Jurnal Multidisiplin West Science, 2025)
Disaster relief operations during flood emergencies are often conducted under conditions of high uncertainty, limited access, and constrained resources. In such contexts, operational decisions regarding prioritization, transportation, and deployment of critical support infrastructure directly affect humanitarian effectiveness and equity. This study examines how satellite-based geohazard assessment can support disaster relief operational planning during the emergency response phase. Using recent flood events in Sumatra as a case study, the analysis draws on satellite imagery to observe flood extent, settlement exposure, access disruption, and housing damage along riverine floodplains. Rather than applying complex predictive or simulation-based models, the study emphasizes how rapid geohazard observation can be translated into operational interpretation to support timely decision-making, including transportation mode selection, prioritization under resource scarcity, and deployment of essential infrastructure such as emergency power supply. The findings indicate that geohazard-informed planning enhances situational awareness and supports more coherent and equitable humanitarian response across multiple intervention domains, including logistics delivery, medical response, psychosocial support, and child-centered relief. A conceptual pathway is presented to illustrate how geohazard assessment informs operational decisions and generates multiplier impacts across disaster relief activities. Beyond its operational relevance, the study highlights the role of evidence-informed learning in strengthening professional practice under uncertainty. The study concludes that integrating geohazard assessment into emergency response practices improves the effectiveness, accountability, and adaptability of humanitarian operations in flood-affected contexts.